2009
DOI: 10.1295/polymj.pj2008220
|View full text |Cite
|
Sign up to set email alerts
|

Development of Aromatic Polymer Electrolyte Membrane with High Conductivity and Durability for Fuel Cell

Abstract: This report describes a design, preparation and evaluation data of a novel polymer electrolyte membrane, which have been successfully developed for the use in fuel cell vehicles (FCV). This membrane is prepared from the aromatic block copolymer, consisting of alternating stiff sulfonic acid-bearing segments and hydrophobic flexible polymeric sub-units. A bicontinuous microphase-separated morphology of the membrane has been attested, contributing to its excellent water resistance with keeping high proton conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 18 publications
3
88
0
Order By: Relevance
“…[15] Still, a number of investigations have recently demonstrated that it is possible to reach high proton conductivities in sulfonated hydrocarbon membranes at low relative humidities (RHs) provided that a percolating phase domain is maintained where the local concentration of acid is kept high. [16,17] This implies that the membrane polymers must carry segments, or blocks, which are highly sulfonated, and that an efficient phase separation between the hydrophilic parts must occur to maintain a high local sulfonic acid concentration in the membrane. At the same time, an excessive water uptake and loss of mechanical strength at high RH must be prevented.…”
Section: Hydroxy-terminated Paes Oligomersmentioning
confidence: 99%
“…[15] Still, a number of investigations have recently demonstrated that it is possible to reach high proton conductivities in sulfonated hydrocarbon membranes at low relative humidities (RHs) provided that a percolating phase domain is maintained where the local concentration of acid is kept high. [16,17] This implies that the membrane polymers must carry segments, or blocks, which are highly sulfonated, and that an efficient phase separation between the hydrophilic parts must occur to maintain a high local sulfonic acid concentration in the membrane. At the same time, an excessive water uptake and loss of mechanical strength at high RH must be prevented.…”
Section: Hydroxy-terminated Paes Oligomersmentioning
confidence: 99%
“…[1][2][3][4] Recently, hydrophilic-hydrophobic aromatic multiblock copolymers have attracted great interest to improve the proton conductivity under low humidity. [5][6][7][8][9][10] Poly( p-phenylene) derivatives bearing sulfonated aromatic side groups have been investigated as PEMs because of their excellent chemical stability based on the fully aromatic structure. [10][11][12][13] Goto et al developed multiblock aromatic copolymers composed of hydrophilic oligo(2-(3-sulfobenzoyl)-1,4-phenylene) segments and hydrophobic aromatic oligomer segments.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Poly( p-phenylene) derivatives bearing sulfonated aromatic side groups have been investigated as PEMs because of their excellent chemical stability based on the fully aromatic structure. [10][11][12][13] Goto et al developed multiblock aromatic copolymers composed of hydrophilic oligo(2-(3-sulfobenzoyl)-1,4-phenylene) segments and hydrophobic aromatic oligomer segments. [10] Hydrolytically labile bonds such as imide groups were not incorporated in the hydrophobic aromatic segments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recently, highly sulfonated moieties 3 or sequenced hydrophilic and hydrophobic groups as block copolymers 4 were claimed to improve proton conductivity under high temperature. However, none of these alternative membranes could compete with Nafion membranes.…”
mentioning
confidence: 99%